The Role of Green Entrepreneurial Intention in Shaping Green Entrepreneurial Behavior: A Literature Review - Wahyono, Tirta; Satriyo, Fuad Rizki; Andriyani, Andriyani (LifeSciFi, 2024)
As the world progresses, environmental issues have become a pressing concern for all nations, including Indonesia. Green entrepreneurship has gained prominence as a viable approach to fostering new business opportunities and economic growth. In the face of Indonesia's entrepreneurial and environmental challenges, aspiring entrepreneurs must adapt to become green entrepreneurs. This research delves into the concepts of Green Entrepreneurial Intention (GEI) and Green Entrepreneurial Behavior (GEB). The study aims to elucidate the variables involved by drawing upon data sources from previous research. A literature review is employed, relying on evidence from existing phenomena and research findings. The Theory of Planned Behavior (TPB) serves as the theoretical framework for exploring the research. The study focuses solely on the empirically supported proposition that GEI positively influences GEB. The findings offer valuable insights for stakeholders regarding the significance of cultivating GEI among individuals through education and training on green entrepreneurship, as well as providing access to capital and mentorship for aspiring green entrepreneurs.